Suppression mechanism of millisecond afterglow in CsI:Tl crystals by Eu²⁺ impurity - Kudin, A.M.; Shkoropatenko, A.V.; Ovcharenko, N.V.; Alekseev, V.D.; Trefilova, L.N.; Shpilinskaya, A.L. (Functional Materials, 2009)
The causes of millisecond afterglow in Csl:Tl crystals have been considered. The two afterglow components with about 5 ms and about 60 ms characteristic time at RT have been shown to be related to the trap disruption at 190 and 215 K. The thermostimulated luminescence peak at 215 K is of extrinsic nature and is associated most probably with barium cations in the form of single dipoles Ba²⁺-Vc⁻. In contrast to Ba²⁺, introduction of Eu²⁺ cations results in the afterglow attenuation. The aggregation of Eu²⁺-Vc⁻ dipoles in a quenched sample has been found to occur during almost 10 min at RT. The afterglow suppression mechanism in Csl:Tl,Eu crystals consists in that not only europium ions but also other Me²⁺ type impurities are involved in the aggregation process. After the solid solution decomposition and metastable aggregate formation, not millisecond but more durable afterglow is observed in the crystals within the second and minute time ranges. Розглянуто причини мілісекундного післясвітіння кристалів Csl:TJ. Показано, що два компоненти післясвітіння з характерними часами -5 та -60 мс при кімнатній температурі пов'язані з руйнуванням пасток при 190 та 215 К. Пік термостимульованої люмінесценції при 215 К має домішкову природу та пов'язаний найімовірніше з катіонами барію у формі окремих диполів Ba²⁺-Vc⁻. На відміну від Ва²⁺, введення катіонів Eu²⁺ призводить до зниження післясвітіння. Показано, що агрегація диполів Eu²⁺-Vc⁻ у загартованому зразку триває не більше 10 хв при кімнатній температурі. Механізм пригнічення післясвітіння в кристалах Csl:TJ,Eu полягає в тому, що до процесу агрегації залучаються не тільки іони європію, але й інші домішки типу Ме²⁺. Після розпаду твердого розчину та утворення метастабільних агрегатів у кристалах спостерігається не мілісекундне, а більш тривале післясвітіння у секундному та хвилинному діапазонах часу. Рассмотрены причины миллисекундного послесвечения кристаллов Csl:TJ. Показано, что два компонента послесвечения с характерными временами -6 и -60 мс при комнатной температуре связаны с разрушением ловушек при 190 и 215 К. Пик термостимулированной люминесценции при 215 К имеет примесную природу и наиболее вероятно связан с катионами бария в виде одиночных диполей Ba²⁺-vc-· В отличие от Ва²⁺, введение катионов Eu²⁺ приводит к снижению послесвечения. Показано, что агрегация диполей Eu²⁺-Vc⁻ в закаленном образце занимает не более 10 мин при комнатной температуре. Механизм подавления послесвечения в кристаллах Csl:TJ,Eu состоит в том, что в процесс агрегации вовлекаются не только ионы европия, но другие примеси типа Ме²⁺. После распада твердого раствора и образования метастабильных агрегатов в кристаллах наблюдается не миллисекундное, а более длительное послесвечение в секундном и минутном диапазоне времен.